Identifikasi Faktor Penentu Kemiskinan di Indonesia Melalui Pendekatan Regresi Linier Berganda - Juniasti Gulo (Pusat Riset dan Inovasi Nasional, 2025)
Poverty in Indonesia remains a significant challenge despite various mitigation programs. This condition is influenced by the complex interaction of social and economic factors, including regional disparities and limited access to basic services. This study aims to identify and analyze the influence of six main factors on poverty levels, namely unemployment rate, average years of schooling, access to clean water, access to healthcare services, per capita GRDP, and population density, using multiple linear regression. The analysis results show that unemployment rate, access to clean water, and healthcare services significantly affect poverty, where higher unemployment and limited access to these services tend to increase poverty levels. Meanwhile, average years of schooling, per capita GRDP, and population density have no significant partial effect. These findings emphasize the importance of policy focus on reducing unemployment and improving access to basic services to effectively lower poverty rates. This study provides an empirical basis for formulating more targeted development strategies to address poverty in Indonesia.